2018
DOI: 10.1002/oa.2709
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joint osteoarthritis in human ancient skeletal remains from Late Holocene in southern Patagonia

Abstract: Low prevalence of caries, high stages of dental attrition (DA), and moderate frequency of antemortem tooth loss (AMTL) were found in skeletal remains of hunter‐gatherers from southern Patagonia. However, osteoarthritis (OA) of temporomandibular joint (TMJ), possible related to oral health, has not been studied so far. The influence of hunter‐gatherer living conditions on the development of TMJ‐OA was scarcely evaluated, and analyses of degenerative changes of TMJ in nonindustrialized groups are needed. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Each had varying levels of AMTL, reflecting the observation that joint wear is associated with tooth loss and attrition (Hodges, ). Suby and Giberto () suggest that dietary patterns may be an aetiological factor for TMJD. Complete wear of the condylar facet in the TMJ was observed in two coastal individuals from pre‐2000 bp .…”
Section: Health and Stressmentioning
confidence: 99%
“…Each had varying levels of AMTL, reflecting the observation that joint wear is associated with tooth loss and attrition (Hodges, ). Suby and Giberto () suggest that dietary patterns may be an aetiological factor for TMJD. Complete wear of the condylar facet in the TMJ was observed in two coastal individuals from pre‐2000 bp .…”
Section: Health and Stressmentioning
confidence: 99%
“…This may suggest that, despite the increasing number of AMTLs in older adults, the overall molar support of the studied individuals may have been well preserved and therefore may not have contributed significantly to any overload of the TMJs in our sample. Nevertheless, a correlation between TMJ-OA and AMTL has been reported in other contexts (e.g., Suby & Giberto, 2019).…”
Section: Dental Factors and Tmjsmentioning
confidence: 90%
“…The prevalence of TMJ-OA in ancient skeletal remains ranges between 2.4% and 38.5%, as reported by . Although studies investigating TMJs in preindustrial populations focused mostly on Aboriginal populations (Richards, 1990;Webb, 1995), research on prehistoric hunter-gatherer populations has also been conducted (Stone et al, 2020;Suby & Giberto, 2019;Tanaka et al, 2004;Visser, 1994). Because the hardness and toughness of food can impact the development of TMJ-OA (Chen et al, 2013;Komino & Shiga, 2017;Liu et al, 2014;Peyron et al, 1997;Tran et al, 2023), it is important to identify the types of food ingested by the populations under study.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier paper, Castro and Aspillaga (1991) show a similar prevalence of osteoarthritis of TMJ in Kaweshkar (17%) and Selk'nam (14%) individuals from the mission on Isla Dawson. In a more recent study, Suby and Giberto (2018) analyzed 25 skulls from pre- and postcontact periods from Southern Patagonia following current criteria (Rando and Waldron 2012). The authors found a frequency of 28% of slight osteoarthritis of TMJ (Figure 3), mostly related to AMTL and older age.…”
Section: Recent Paleopathological Researchesmentioning
confidence: 99%